2020
DOI: 10.2147/itt.s273327
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic Vaccines for HPV-Associated Malignancies</p>

Abstract: Human papillomavirus (HPV)-related malignancies are responsible for almost all cases of cervical cancer in women, and over 50% of all cases of head and neck carcinoma. Worldwide, HPV-positive malignancies account for 4.5% of the global cancer burden, or over 600,000 cases per year. HPV infection is a pressing public health issue, as more than 80% of all individuals have been exposed to HPV by age 50, representing an important target for vaccine development to reduce the incidence of cancer and the economic cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 156 publications
(198 reference statements)
1
68
0
Order By: Relevance
“…The development of therapeutic vaccines against hrHPV could help women who are already infected by stopping progression, triggering regression of lesions, and preventing recurrence of disease ( 166 ). Currently, there is no therapeutic HPV vaccine approved by the US Food and Drug Administration ( 167 ). While the use of therapeutic vaccines to treat invasive cervical cancer or other HPV-related cancers is beyond the scope of this review, many of the completed and currently ongoing trials (see NCT02481414, NCT00054041, NCT01022346, NCT03870113 as examples, not a comprehensive list) use CIN and/or HSIL as the treatment target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of therapeutic vaccines against hrHPV could help women who are already infected by stopping progression, triggering regression of lesions, and preventing recurrence of disease ( 166 ). Currently, there is no therapeutic HPV vaccine approved by the US Food and Drug Administration ( 167 ). While the use of therapeutic vaccines to treat invasive cervical cancer or other HPV-related cancers is beyond the scope of this review, many of the completed and currently ongoing trials (see NCT02481414, NCT00054041, NCT01022346, NCT03870113 as examples, not a comprehensive list) use CIN and/or HSIL as the treatment target.…”
Section: Resultsmentioning
confidence: 99%
“…While the use of therapeutic vaccines to treat invasive cervical cancer or other HPV-related cancers is beyond the scope of this review, many of the completed and currently ongoing trials (see NCT02481414, NCT00054041, NCT01022346, NCT03870113 as examples, not a comprehensive list) use CIN and/or HSIL as the treatment target. Smalley Rumfield et al recently conducted a review of peptide, protein, viral vector, bacterial vector, cell, DNA, and RNA-based therapeutic vaccines as well as multi-platform and combination therapies, which demonstrate diverse potential therapies that can be useful in LMIC settings, while presenting new and different challenges ( 167 ).…”
Section: Resultsmentioning
confidence: 99%
“…This test compound, exerting outstanding activity against both HPV-18 and HPV-16 positive cervical cancers, might be of great importance in the design of anticancer agents targeting cervical carcinomas, since the majority of these carcinomas are caused by these two types of HPV. For invasive cervical cancer, HPV-16 is the most prevalent type (approximately 60%), HPV-18 is the second (15%), and HPV-45 is the third most common type 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Low-risk HPV types are those that cause genital warts but are not carcinogenic, including types 6,11,42,43, and 44 [16,18]. High-risk HPV types are considered carcinogenic, and include 16,18,31,33,34,35,39,45,51,52,56,58,59,66,68, and 70 [6,16]. Wentzensen et al [19] confirmed that HPV integration sites are randomly distributed over the whole genome, with a clear predilection for fragile sites.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their association with cervical cancer and precursor lesions, HPVs can also be grouped into high-risk and low-risk HPV types. Low-risk HPV types are those that cause genital warts but are not carcinogenic, including types 6, 11, 42, 43, and 44 [ 16 , 18 ]. High-risk HPV types are considered carcinogenic, and include 16, 18, 31, 33, 34, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68, and 70 [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%